Changing trends of chronic myeloid leukemia in greater Mumbai, India over a period of 30 years - Rajesh P Dikshit; Rajini Nagrani; Balkrishna Yeole; Shravani Koyande; Shripad Banawali (Indian Journal of Medical and Paediatric Oncology)
Background: Little is known about burden of chronic myeloid leukemia (CML) in India. There is a recent interest to observe incidence and mortality because of advent of new diagnostic and treatment policies for CML. Materials and Methods: We extracted data from the oldest population-based cancer registry of Mumbai for 30 years period from 1976−2005 to observe incidence and mortality rates of CML. We classified the data into four age groups 0−14, 15−29, 30−54 and 55−74 to observe incidence rates in the respective age groups. Results: The age specific rates were highest for the age group of 55−74 years. No significant change in trends of CML was observed for 30 years period. However, there was a significant reduction in incidence rate for recent 15-years period (Estimated average annual percentage change=-3.9). No significant reduction in mortality rate was observed till 2005. Conclusion: The study demonstrates that age-specific rates for CML are highest in age group of 55-74 years, although they are lower compared to western populations. Significant reduction in incidence of CML in recent periods might be because of reduced misclassification of leukemias. The data of CML has to be observed for another decade to witness reduction in mortality because of changes in treatment management.